Antitrypanosomal Activity & Docking Studies of Isolated Constituents from the Lichen Cetraria islandica: Possibly Multifunctional Scaffolds - Ogbaji Igoli, John; Irvine Gray, Alexander; Jean Clements, Carol; Kantheti, Poorna; Kumar Singla, Rajeev (Current Topics in Medicinal Chemistry, 2014)
Chemical investigation of the lichen Cetraria islandica has led to the isolation of four compounds identified as protolichesterinic acid, lichesterinic acid, protocetraric acid and fumarprotocetraric acid. Their structures were characterized using their physical and spectroscopic data. Using an Alamarblue™ 96 well microplate assay, these compounds were tested to evaluate their trypanocidal activity against Trypanosoma brucei brucei. Protolichesterinic acid (MIC = 6.30 μM) and lichesterinic acid (MIC = 12.5 μM) showed very significant activity against the test organism. Docking studies (GRIP technique) of these molecules revealed their strong affinity towards possible targets of Trypanosoma brucei such as riboflavin kinase, sterol-14α-demethylase (CYP51), rohedsain and glutathione synthetase. Hydrophobicity played a significant role in their antitrypanosomal activity.
Keywords: iceland moss